Learning Concepts Learning Approach Models in Improving Students' Understanding of Mathematical Concepts - Anggraini, Septi (Lembaga Riset Mutiara Akbar, 2023)
Understanding mathematical concepts is the ability to master material and students' ability to understand, absorb, master, and apply it in mathematics learning. One of the problems that is often encountered in learning mathematics is usually when students cannot work on mathematics problems due to the students' lack of understanding of concepts. Many factors influence students' lack of understanding of concepts, one of which is learning patterns. The Concept Learning Learning Model is an approach to learning that aims to help students understand and master concepts that cover a field of study or subject.